Health care providers' experiences and perceptions participating in a chronic pain telementoring education program: A qualitative study. Issue 1 (1st January 2020) - Zhao, Jane; Salemohamed, Naima; Stinson, Jennifer; Carlin, Leslie; Seto, Emily; Webster, Fiona; Furlan, Andrea D.
ABSTRACT: Background: Chronic pain affects one in five Canadians. Frontline health care providers (HCPs) manage the majority of patients with chronic pain yet receive minimal training to do so. The Extension for Community Healthcare Outcomes (ECHO) model™ is an education intervention aimed at HCPs (not patients) to support and improve care in underserviced communities. ECHO Ontario Chronic Pain and Opioid Stewardship (ECHO PAIN) is an adaptation of the ECHO model where the program goals are to support and improve chronic pain and opioid management in the province of Ontario, Canada. Aims: This study aimed to investigate the perceptions of HCPs participating in ECHO PAIN. Methods: Thirteen HCPs attending ECHO PAIN participated in in-depth semistructured phone interviews. Resulting data were analyzed through a qualitative descriptive lens. Results: Analysis uncovered four themes: (1) HCPs' motivation for joining ECHO PAIN, (2) interprofessional collaboration through ECHO PAIN, (3) the use of opioids for pain management, and (4) barriers and facilitators to participation and satisfaction in ECHO PAIN. HCPs joined ECHO PAIN because of their struggles managing their complex patients with chronic pain. HCPs also recognized the importance of interprofessional collaboration in pain management and shared examples of integration of different professional approaches in their clinical teams. Opioids for pain management remained a controversial issue, and ECHO served as an opportunity to decrease this knowledge gap. Finally, HCPs described how time constraints, organizational support, and session structure acted as barriers to their participation and satisfaction in the ECHO PAIN program; technology mediated satisfaction. Conclusions: This study was the first in Canada to explore the motivations of HCPs in attending a chronic pain telementoring program as well as to examine the interprofessional effects of participation. HCPs increased their knowledge about management of chronic pain and increased their interprofessional approach.